Stepping from Graph Transformation Units to Model Transformation Units - Kreowski, Hans-Jörg; Kuske, Sabine; von Totth, Caroline (Electronic Communications of the EASST, 2010)
Graph transformation units are rule-based entities that allow to transform source graphs into target graphs via sets of graph transformation rules according to a control condition. The graphs and rules are taken from an underlying graph transformation approach. Graph transformation units specify model transformations whenever the transformed graphs represent models. This paper is based on the observation that in general models are not always suitably represented as single graphs, but they may be specified as the composition of a variety of different formal structures such as sets, tuples, graphs, etc., which should be transformed by compositions of different types of rules and operations instead of single graph transformation rules. Consequently, in this paper, graph transformation units are generalized to model transformation units that allow to transform such kind of composed models in a rule-based and controlled way. Moreover, two compositions of model transformation units are presented.